KELAYAKAN LOKASI DAN FINANCIAL PEMBANGUNAN PABRIK PENGOLAHAN KARET SKALA KECIL DI KECAMATAN BANYUASIN III KABUPATEN BANYUASIN - Nasir Nasir; Ekanovi Aktiva (JURNAL AGRIBISNIS TERPADU, 2022)
The research entitled Feasibility Location and Financial of Development Small-Scale Rubber Processing Factory in Banyuasin III District, Banyuasin Regency, by Nasir and Ekanopi Aktiva. The research aims to: Analyzing the location and financial feasibility of constructing a small-scale rubber processing plant. This research was conducted in Langkan Village, Banyuasin III District, Banyuasin Regency. The research was carried out for 5 (five) months, starting from July to November 2021.  The research method used is a survey method in the rubber processing industry.  The population in this study is the owner of the rubber processing industry. The sampling method used is saturated sampling, that is, the entire population is used as a sample in this study.  Data collection was carried out through direct interview techniques using research instruments on business owners of the rubber processing industry. Location feasibility analysis has used qualitative methods (Rating Procedure) and financial feasibility has used NPV, IRR, B/C Ratio and Payback Period.  The results of the study concluded that the construction of a small-scale rubber processing plant in Langkan Village, Banyuasin III District, Banyuasin Regency met the requirements because it was supported by several factors, namely: sufficient raw materials are available, technology is available at low cost and easy to obtain, production capacity needs to be increased, factory location easily accessible, adequate infrastructure and available manpower. The analysis of the financial aspect concluded that the construction of a small-scale rubber processing plant was feasible, with an NPV value of Rp. 6,765,056,434.24, IRR = 152.55%, B/C ratio = 0.11 and payback period = 1.46 years (1 year, 5 months, 18 days.